The sound(s) of subjection: Constructing American popular music and racial identity through Blacksound. Issue 1 (2nd January 2017) - Morrison, Matthew D.
Abstract : "I will be rich in black fun." 1 –– Charles Mathews, 1823 This article considers Saidiya Hartman's formulation of "Terror and Enjoyment" in Scenes of Subjection to explore how the subjection and commodification of the aesthetic and cultural practices of African Americans during slavery laid the foundation for how the sounds produced by these peoples became racialized, stereotyped, and consumed by the masses in the development of popular music. The author has neologized the concept of Blacksound as a theory of historical embodiment to trace the ephemerality and materiality of the sounds produced by black bodies within the history of popular music in the United States, and to serve as a complement to discourses of race based in visuality. Blacksound is used to explore the ways in which black bodies and their myriad aesthetic practices have been subjected through spectacular and quotidian popular performances during enslavement, through emancipation, and persisting into the structuring of our (post)modern economies of popular entertainment and identity. Through Blacksound and Hartman, this article also considers how the scripting, commodification, and embodiment of these sonic performances by both black and non-black bodies served as a vehicle for self-imagination and the construction of race and whiteness in U.S. history.